KANDUNGAN FORMALIN PADA BAKSO DAN TAHU SETELAH DILAKUKAN BEBERAPA VARIASI PEREBUSAN - Angki Purwanti Purwanti; Siti Rismini Rismini; Bagya Mujianto Mujianto (Poltekkes Kemenkes Jakarta III, 2014)
Formalin, which is prohibited in food by Regulation of Ministry of Health No 033 year 2012 used largely, especially on proteinated food such as meatball and tofu. Decreasing formalin content in food is expected to solve the problem. Formalin is bonded by protein form methylene substance that can be hydrolyzed to protein and formalin by heating. The research aims at getting description about formalin content on meatball and tofu after boiling by using variation of water volume, time and boiling technique. Formalin content is analyzed spectrophotometrically after being reacted by chromotropic acid. Formalin content decreases 35, 39,45, 38 and 40% on meatball, while on tofu 43, 56, 55, 60 and 48% after boiling by 350, 450, 550, 650 and 750 ml of water, respectively. Boiling for 5, 10, 15 and 20 minutes without changing of boiling water reduce formalin content 26, 43, 51, and 60% in meatball and 35, 41, 51 and 66% in tofu. Boiling samples for 5,10,15 and 20 minutes by changing of boiling water every 5 minutes reduce formalin content by 37, 64, 73 and 81% in meatball and 23, 29, 51 and 75% in tofu. Increasing boiling adds energy to hydrolyze the methylene substance. Decreasing fomalin content is influenced by boiling time and changing the boiling water, but not by the volume of boiling water. It is suggested to boil meatball and tofu for 20 minutes by changing the water every 5 minutes to reduce the formalin content.